2017
DOI: 10.1002/ece3.3010
|View full text |Cite
|
Sign up to set email alerts
|

Global realized niche divergence in the African clawed frog Xenopus laevis

Abstract: Although of crucial importance for invasion biology and impact assessments of climate change, it remains widely unknown how species cope with and adapt to environmental conditions beyond their currently realized climatic niches (i.e., those climatic conditions existing populations are exposed to). The African clawed frog Xenopus laevis, native to southern Africa, has established numerous invasive populations on multiple continents making it a pertinent model organism to study environmental niche dynamics. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 80 publications
(148 reference statements)
2
27
1
Order By: Relevance
“…Additionally, a recent study which modelled the potential distribution of X. laevis in western France by using bioclimatic data, showed that the maximal expected invasive range is much larger than our updated range (Rödder et al, 2017). The capacity of the species to cross major watercourses raises concerns about the occurrence of natural barriers to the expansion of X. laevis in western Europe.…”
Section: Discussionmentioning
confidence: 65%
“…Additionally, a recent study which modelled the potential distribution of X. laevis in western France by using bioclimatic data, showed that the maximal expected invasive range is much larger than our updated range (Rödder et al, 2017). The capacity of the species to cross major watercourses raises concerns about the occurrence of natural barriers to the expansion of X. laevis in western Europe.…”
Section: Discussionmentioning
confidence: 65%
“…One such initiative in Europe saw members from four EU countries funded to work jointly on the impacts of the invasive African clawed frog , X. laevis : INVAXEN ( ). This initiative has added 15 published articles on this species, nearly doubling the available data on their invasive populations ( Courant et al, 2017 ; Louppe, Courant & Herrel, 2017 ; Rödder et al, 2017 ). Funded by BIODIVERSA, this call did not include funding for studies on populations in non-participating EU countries (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Since the African clawed frog (Xenopus laevis), which comes from South Africa, has created numerous invasive populations on several continents, it has become a convenient model organism for the study of environmental issues (Rödder et al 2017). The African amphibian Xenopus laevis is generally considered to be an invasive species which constitutes a threat not only to local fauna but also to biodiversity the world over, as it has a strong invasive potential (Tinsley et al 2015).…”
Section: Discussionmentioning
confidence: 99%